PELATIHAN PEMBUATAN KEMASAN PRODUK UKM SEBAGAI UPAYA MENINGKATKAN PENDAPATAN UKM - Asteria, Beta; Nugroho, Mohammad Awal Satrio; Sulastiningsih, Sulastiningsih; Laili, Ina Rizqi; Mawaddah, Sulalatul; Abadi, Bintang Kasih (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2024)
In the Kotabaru village of Yogyakarta there are SMEs that are struggling to contribute to growing the economy in Indonesia. In winning the competition SMEs need to always innovate. One of them is how to win the hearts of buyers to decide to buy these SME products instead of other products. Not yet optimal product packaging produced by Kotabaru SMEs requires a solution to carry out community service activities with the theme of SME product packaging training. The method in this community service activity is carried out by means of training, demonstration and practice. Lectures are conducted to provide education about the importance and usefulness of packaging to training participants, namely Kotabaru SMEs. Demonstrations were carried out by means of the service team showing the materials used in the packaging process then the service team provided examples of finished packaging that could be added to SME products. And the service participants practiced making a bouquet of SME products. The community service activities went well. Participants followed the training with enthusiasm. Participants understood the importance of attractive and informative packaging. The results of the training were that SME participants were able to make beautiful and attractive product packaging. Attractive SME products will increase selling value, increase purchases of SME products as an effort to increase SME income.